Pilot case study on rhythmic gymnastics and dyslexia - Senatore, B.; Valentini, M.; Federici, A.; D'Elia, F. (Journal of Human Sport & Exercise, 2019)
Rhythmic gymnastics is an Olympic sport with qualifying and coordinating features characterized by "small tools". The competitive program includes both individual and team performances. An individualist gymnast presents four different routines, each with a different tool, while the team presents two different compositions, one with the same type of tool and the other with two types of tools. Dyslexia is a learning disorder, the failure of the development of hemispheric dominance or conflicts of dominance between the two hemispheres. In addition to having learning problems, people suffering from dyslexia also have problems in cognition of their bodies within space and with the musical rhythm. The aim is to analyse a case of dyslexic athlete inherent to performance, self-esteem and sociality. Through the case study and ethnographic approach it was found that the gymnast manages to achieve the same results as the other gymnasts who train with her, but showing a small difficulty in teamwork. These results encourage to explore the links between activities and data because you have in front of you an athlete to all intents and purposes, with every pros and cons that every human being can show, even if in this case the corrections must be made in a more patient way and for the results you have to wait a little more time.